Kajian pustaka: Perundungan berbasis teknologi di tempat kerja - Germanikus Clintonis Fernandez (University of Merdeka Malang, 2020)
The purpose of this study to increase awareness about the phenomenon of cyberbullying, especially in the workplace, which is still of little concern by some researchers, especially in literary studies. The Literature search was performed using various databases including science direct and google scholar. The criteria used are articles published in 2012-2018. Based on the articles collected, the results show that definitions of cyberbullying cannot limit the cultural influences ideology and the variety and frequency of forms of cyberbullying and contain various factors related to the factors that influence cyberbullying in the workplace. Future research is expected to find out whether individuals involved in cyberbullying are sued or who are involved and who are related to the profession or who use the latest applications and technology as container for cyberbullying activities in the workplace.